Biomaterials: Towards the Development of Smart 3D "Gated Scaffolds" for On‐Command Delivery (Small 23/2014). Issue 23 (December 2014) - Mas, Núria; Arcos, Daniel; Polo, Lorena; Aznar, Elena; Sánchez‐Salcedo, Sandra; Sancenón, Félix; García, Ana; Marcos, M. Dolores; Baeza, Alejandro; Vallet‐Regí, María; Martínez‐Máñez, Ramón
<x xml:space="preserve">Abstract</x> Gated 3D scaffolds for controlled release in bone remodeling processes using capped silica mesoporous nanoparticles and classical porous biomaterials are reported on page 4859 by M. Vallet‐Regí, R. Martínez‐Máñez, and co‐workers. The designed "gated scaffold" remains tightly capped, yet is able to deliver the cargo in the presence of acid phosphatase. The innovative combination of gated nanoparticles with 3D supports is envisioned to be a promising tool in the design of smart scaffolds for regenerative medicine and bone cancer therapy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>